Is It Cost-Effective To Increase Aspirin Use in Outpatient Settings for Primary or Secondary Prevention? Simulation Data from the REACH Registry Australian Cohort - Ademi, Z.; Liew, D.; Hollingsworth, B.; Steg, P.; Bhatt, D.; Reid, Christopher (2013)
Aims: To describe aspirin use in primary and secondary prevention and to determine the incremental costs-effectiveness ratio (ICER) per life year gain (LYG) of aspirin use among subjects with, or at high risk of atherothrombotic disease. Design and Subjects: To project the cost-effectiveness of aspirin over 5 years of follow-up, a Markov state transition model was developed with yearly cycles and the following health states: "Alive" (post-CAD) and "Dead." The model compared current coverage observed among 2361 subjects using the prospective Australian subset of Reduction of Atherothrombosis for continued Health (REACH) registry, and hypothetical situation whereby all subjects assumed to be treated. Costs were calculated based on the Australian government reimbursed data for 2010. Main outcome measures: ICER per LYG for increased use of aspirin. Results: The use of aspirin in current group varied from 67% to 70%. The base-case analysis showed that increasing aspirin use among subjects with existing CAD in outpatient settings was cost saving, while increasing use of aspirin in primary prevention equated to an ICER of AUD 7126 per LYG. Conclusion: Among subjects with existing CAD aspirin use was shown to be a dominant choice of treatment. However, among patients without existing cardiovascular disease (primary prevention), increased uptake of aspirin was cost effective but with uncertain benefit, with two hemorrhagic bleeding events occurring for every life saved. © 2011 Blackwell Publishing Ltd.